One Vehicle Routing Problem as the Best Solution for a Hangout Catering Company Expansion Plan with Lingo Software - Mohammad Riski Borman; Mirani Oktavia (LPPM, 2020)
Every company that has a desire to expand its working area or can be termed an expansion plan is an indication that the company has the will to continue and develop as well as proof that the company has good business prospects in the future. There are many things that can be done in an expansion effort for the company, including expanding the product marketing area. The expansion of the product marketing area will make the company face the problem of determining the route of product delivery so that it reaches all customers who are expected to pass the shortest mileage. In this studied, we examined the routes that the Hangout Catering Company had to take in order to obtain the best touring to reach the ten places that were expansion targets with three operating scenarios based on the number of vehicles used. The solution to this problem is obtained with the help of Lingo software.